Survey of ICT and Education in Africa : Angola Country Report - Isaacs, Shafika (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Three decades of civil war have decimated the country's infrastructure and education system with large sections of the population still in dire straits, and high numbers of school-age children are out of school. Amid these challenges, the government has established a National Commission on Information Technology, now called the National Information Technology Agency, which has been given the task of developing a national ICT policy. There are a few programs and projects specifically on ICTs in education in the country, although these are largely small-scale, short-term initiatives.